Pengembangan Geopark Rajamandala Dalam Mendukung Pembangunan Nasional dan Daerah Yang Berkelanjutan - Izhar Rismawan; Ima Amaliah (UNISBA Press, 2023)
Abstract. Potential development in each region is carried out in a structured manner to improve the economy and welfare of the community. One method of developing regional potential is by applying the Geopark concept in an area. Since 2018, GRM has been registered as a National Geopark by the KBB local government, but until now there has been no significant progress due to the lack of community involvement and there is a conflict of interest between the government and the KBB community. Based on this phenomenon, the problems in this study are formulated as follows: (1) How is the development of Rajamandala Geopark to become a national Geopark? (2) What are the effects of Rajamandala Geopark development for the people of KBB? (3) What are the factors that can support and hinder the development of Rajamandala Geopark to become a national Geopark. Researchers used a qualitative method with a case study approach. The population chosen in this study was the people of KBB in Citatah and Gunungmasigit Villages totaling 37557 people. Sampling in this study using purposive sampling technique, obtained the number of research samples as many as 5 community key informants. The data collection techniques used in this research are interviews, observation, documentation and literature study. The data analysis technique used in this research is qualitative descriptive analysis technique. The results of this study are: There are obstacles in the development of Rajamandala Geopark to become a national Geopark, besides that the development of Rajamandala Geopark has a positive influence on the people of KBB and there are 4 supporting factors, and 4 inhibiting factors in the development of Rajamandala Geopark. Abstrak. Pengembangan potensi di setiap daerah dilakukan secara terstruktur untuk meningkatkan ekonomi dan kesejahteraan masyarakat. Salah satu metode pengembangan potensi daerah adalah dengan menerapkan konsep Geopark di sebuah wilayah. Sejak tahun 2018, GRM telah didaftarkan menjadi Geopark Nasional oleh pemerintah daerah KBB, namun hingga saat ini tidak ada kemajuan yang signifikan karena kurangnya keterlibatan masyarakat dan terdapat benturan kepentingan antara pemerintah dan masyarakat KBB. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana pengembangan Geopark Rajamandala untuk menjadi Geopark nasional? (2) Apa saja pengaruh dari pengembangan Geopark Rajamandala bagi masyarakat KBB? (3) Apa faktor faktor yang dapat mendukun dan menghambat pengembangan Geopark Rajamandala untuk menjadi Geopark nasional?. Peneliti menggunakan metode kualitatif dengan pendekatan studi kasus. Populasi yang dipilih dalam penelitian ini adalah masyarakat KBB di Desa Citatah dan Gunungmasigit sejumlah 37557 masyarakat. Pengambilan sampel pada penelitian ini menggunakan teknik purposive sampling, diperoleh jumlah sampel penelitian sebanyak 5 informan kunci masyarrakat. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah, wawancara, observasi, dokumentasi dan studi pustaka. Adapun teknik analisis data yang digunakan dalam penelitian ini adalah teknis analisis deskriptif kualitatif. Hasil dari penelitian ini adalah: Terdapat kendala dalam pengembangan Geopark Rajamandala untuk menjadi Geopark nasional, selain itu pengembangan Geopark Rajamandala memiliki pengaruh positif terhadap masyarakat KBB dan terdapat 4 faktor pendukung, dan 4 faktor penghambat dalam pengembangan Geopark Rajamandala.